SISTEM INFORMASI PENGELOLAAN DATA LAUNDRY PADA RUMAH LAUNDRY BEKASI - Susy Rosyida; Verry Riyanto (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2019)
Laundry house is a business engaged in services in washing and drying, especially clothing. To serve the public in the field of laundry services, the laundry house in managing the data is still done manually and has not been computerized so there are still errors in the transaction process. Problems that occur in a laundry house such as incorrectly recording the type of package, the calculation is still using a calculator tool, in making the report must see the notes that have been collected previously, must see previous records recorded in the ledger, and be vulnerable to losing previous note notes so that it takes a long time and the results obtained are less accurate. The purpose of this study is to build a laundry data management program using the waterfall method which consists of 5 stages, namely, software requirements analysis, design, programming code, testing and support or maintenance. While the data collection is through observation, interviews and searching for literature related to this research so that it can solve problems related to laundry data management activities, especially in the process of receiving laundry services transactions to be more effective and efficient and can improve service to customers. The results of the study show that this laundry data management program can help and simplify the process of receiving laundry services at the laundry house.